Liquid smoke collection system from pyrolisis of coconut shell - Zainol, Ismail; Che Razali, Rafiq Akram; Ibrahim, Husni; Syed Abdul Aziz, Saripah Salbiah; Mohamad Ali, Nor Azah; Jaafar, Che Nor Aiza; Mohd Yusof, Nur Sakinah; Shafiee, Maria (Knowledge Transfer Programme – Ministry of Higher Education, Malaysia, 2015)
Coconut shell is widely used for making charcoal for activated carbon production. The simple method to produce charcoal is open burning of coconut shell, but this was contributing significantly to CO2 and methane emissions. This method not only pollutes the environment, but also contributes to health hazard to nearby residents. Therefore, from this awareness a special pyrolysis system was created to trap the smoke and condense them into liquid smoke. The pyrolysis system consists of 200 litre stainless steel pyrolysis heating chamber, 5 m long transfer tube with a diameter of 0.30 m, 20 litre condensation tank and 5 litre of collecting tank. The composition of liquid smoke was confirmed using GCMS analysis. The first condensate was collected after 60 minutes with temperature of pyrolysis chamber was recorded as 140 oC. The pyrolysis process was completed after 4 hours and the percentage yield (w/w) was 32% charcoal, 32% liquid smoke, 22% heavy tar. The GCMS analysis on the distilled liquid smoke detected 9 compounds with main composition was phenolic with 72%, 11% of furfural and 2% of butanoic acid. The heavy tar however consist of 80% phenolic, 1% of furfural, 2% of butanoic acid and 2% of pyran. Other compounds were present in small quantities. The present of phenolic compound made this materials have high potential to be used as food preservative and flavor.